the Verdictive Speech Acts Produced by the Teacher in a Classroom Activity: An Analysis Based on Charles’s Theory - Kartika Putri, Adinda (Intertwine: Journal of English Language, Literary, and Cultural Studies, 2025)
All of the teacher's utterances during classroom activities have meanings that are not just information but also express certain things. Understanding linguistics is very crucial, especially in the field of speech acts that are directly related to communication and interaction between people. There are many types of speech acts and not all of them have been studied, one of which is the verdictive speech act. The purpose is to examine the types of verdictive speech acts that are often uttered by the teacher in the class. This research uses descriptive qualitative research. The data were collected using observation in class VII-E at SMPN 2 Gudo, Jombang. The research data were in the form of teacher utterances using Charles W. Kreidler's speech act theory. The data were analyzed using Miles and Huberman's model. The results showed that the type of verdictive speech act that was often expressed by the teacher was praise with 10 utterances out of 11 utterances and 1 utterance for congratulation. This research concluded that the types of verdictive speech acts that have been found by the researcher are praise and congratulation. But other types of verdictive speech acts have not been found in this research.